Influence of microstructure on stainless steel 316L lattice structures fabricated by electron beam and laser powder bed fusion - Zeng, Zhuohong (2023)
In this work, three-dimensional stainless steel 316L re-entrant lattice structures were fabricated by two mainstream powder bed fusion (PBF) techniques, namely electron beam PBF (EB-PBF) and laser PBF (L-PBF). Different grain morphology and crystallographic textures were found in the EB-PBF and L-PBF samples, which significantly influenced their mechanical properties through microscopic deformation. The EB-PBF and L-PBF samples achieved energy absorption capacities of 627.4 mJ/mm3 and 834.8 mJ/mm3, respectively, at a lattice relative density of ∼24%. The EB-PBF sample exhibited equiaxed and elongated grains, while elongated grains were primarily observed in the L-PBF sample. The dominant deformation mechanism of the EB-PBF sample was obtained through dislocation. In contrast, the dislocations trapped inside the solidification cellular walls and deformation-induced twinning were the dominant deformation mechanisms for the L-PBF sample, which contributed to its superior compressive strength and energy absorption capacities. This work provides insights into the enhancement of the mechanical properties of the additively manufactured metallic lattice structures through microstructural control.